The Effectiveness of Averrhoa Bilimbi L. Juice Combined with Stevia on Reducing Blood Pressure - Miftahunnisa Danti Ilato; Ida Leida Maria; Ridwan Amiruddin; Wahiduddin; Apik Indarty Moedjiono (International Journal of Medical Toxicology and Legal Medicine, 2024)
Management of hypertension can be done through complementary therapy using herbal plants, one of which is Averrhoa bilimbi L. which contains active compounds that can lower blood pressure. This study aims to determine the effectiveness of giving stevia-combined star fruit juice in lowering blood pressure in patients with hypertension. This experimental research uses a Non Randomized Pretest-Posttest Control Group study design. A total of 70 respondents who met the criteria were divided into two groups, namely 35 people in the intervention group who were given stevia-combined star fruit juice and consumption of antihypertensive drugs and 35 people in the control group who only took antihypertensive drugs. Blood pressure was measured before and after 7 days of intervention and analyzed using t-dependent. The mean blood pressure measurement in the intervention group before treatment was 148.08 mmHg and after was 134.28 mmHg, with a p value = 0.000. While in the control group, the average blood pressure measurement before treatment was 147.37 mmHg and after 140.91 mmHg, with a p value = 0.000. Consumption of drugs and herbal formulations such as stevia-combined star fruit juice can be an alternative that has minimal side effects and reduces toxic effects compared to synthetic drugs.